First-principles study of lead-free Ge-based 2D Ruddlesden–Popper hybrid perovskites for solar cell applications. Issue 35 (25th August 2022) - Babaei, Maryam; Ahmadi, Vahid; Darvish, Ghafar
Abstract : Recently, 2D halide perovskites have attracted attention because they are excellent photo absorbing materials for perovskite solar cells. Abstract : Recently, 2D halide perovskites have attracted attention because they are excellent photo absorbing materials for perovskite solar cells. To date, the majority of 2D perovskite-based devices have been made of Pb, a material with toxic properties and environmental concerns. Thus, lead-free alternatives are essential to enable the expansion of photovoltaic systems based on perovskites. Herein, we examine the structural, electronic, optical and stability properties of Pb-free 2D Ruddlesden–Popper (RP) perovskites (BA)2 (MA) n −1 Ge n I3 n +1 (BA = CH3 (CH2 )3 NH3 + ; MA = CH3 NH3 + ; n = 1-5, and ∝) by using DFT calculations and comparing the results to their Pb-based counterparts (BA)2 (MA) n −1 Pb n I3 n +1 ( n = 1–5, and ∝). Theoretical analysis indicates that Pb and Ge-based 2D perovskites are significantly more thermodynamically stable than their corresponding 3D materials. A more accurate bandgap is achieved using the HSE06 + SOC scheme and compared to the findings of the PBE and PBE + SOC. These materials are direct bandgap semiconductors. Due to spin–orbit coupling, Pb-based perovskite displays higher Rashba energy splitting than Ge-based ones. The bandgap changes from 2.37 eV ( n = 1) to 1.79 eV ( n = 5), and from 1.92 eV ( n = 1) to 1.56 eV ( n = 5) for Pb and Ge-based perovskites, respectively. The bandgap of all Ge-based perovskites is lower than their corresponding Pb-based ones. We show that the 2D perovskites could serve as hole-transporting materials when they are alongside 3D perovskites. The trade-off between thermodynamic stability and absorption coefficient of the considered compounds indicates that 2D RP perovskites BA2 MA4 Ge5 I16 are promising Pb-free halide semiconductors for solar cell applications.